2015
DOI: 10.1212/wnl.0000000000002028
|View full text |Cite
|
Sign up to set email alerts
|

Motion discrimination in dementia with Lewy bodies and Alzheimer disease

Abstract: Differential deficits in detecting direction of simple horizontal motion suggest that dorsal processing stream dysfunction is greater in DLB and PDD than in AD dementia. Therefore, impaired performance on simple visual motion discrimination tasks that specifically engage occipitoparietal brain regions suggests the presence of Lewy body pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Conversely, controls had greater impairment of direction than motion detection in the same task, suggesting that complex motion detection rather than directionality may best differentiate AD dementia from normal aging (Liu et al, 2019). This is supported by a study demonstrating that AD dementia patients and controls perform similarly on a horizontal motion discrimination task (Landy et al, 2015). Although there are limited recent studies on motion in MCI, past studies have shown similar deficits in higher-level motion tasks.…”
Section: High-level Visual Functionmentioning
confidence: 86%
“…Conversely, controls had greater impairment of direction than motion detection in the same task, suggesting that complex motion detection rather than directionality may best differentiate AD dementia from normal aging (Liu et al, 2019). This is supported by a study demonstrating that AD dementia patients and controls perform similarly on a horizontal motion discrimination task (Landy et al, 2015). Although there are limited recent studies on motion in MCI, past studies have shown similar deficits in higher-level motion tasks.…”
Section: High-level Visual Functionmentioning
confidence: 86%
“…Cognitive impairment (Addenbrooke's Cognitive Examination‐Revised,7 FAS Verbal Fluency,8 Trail Making Tests A and B,9 Graded Naming Test,10 Rey Auditory Verbal Learning Test,11 and computerized tests of simple and choice reaction times, digit vigilance, line angle discrimination, and motion detection12, 13, 14)…”
Section: Methodsmentioning
confidence: 99%
“…A thorough clinical assessment was carried out including measures of the following: –Cognitive impairment (Addenbrooke's Cognitive Examination‐Revised, FAS Verbal Fluency, Trail Making Tests A and B, Graded Naming Test, Rey Auditory Verbal Learning Test, and computerized tests of simple and choice reaction times, digit vigilance, line angle discrimination, and motion detection) –Functional impairment (Bristol and Instrumental Activities of Daily Living Scales) –Neuropsychiatric symptoms (Geriatric Depression Scale, Clinician Assessment of Fluctuations, Dementia Cognitive Fluctuations Scale, Neuropsychiatric Inventory) –Parkinsonism (revised UPDRS). …”
Section: Methodsmentioning
confidence: 99%
“…Many Lewy body patients present with ANS dysfunction, including urinary incontinence, constipation, erectile dysfunction, coronary dysfunction, or orthostatic hypotension, which increases the likelihood of injury due to falling [25,26]. Lewy body patients sometimes present with sensory dysfunction, losing their sense of smell (anosmia) [27], and/or seeing colors differently [28]. Some Lewy body patients initially present with late life onset depression, with or without visual or auditory hallucinations, delusions, and anxiety [29].…”
Section: Symptomatic Manifestations Of α-Synuclein Pathologymentioning
confidence: 99%